2023
DOI: 10.1101/2023.02.21.23286267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multicenter analysis of atrioesophageal fistula rates before and after adoption of active esophageal cooling during atrial fibrillation ablation

Abstract: Background: Active esophageal cooling reduces the incidence of endoscopically identified severe esophageal lesions during radiofrequency (RF) catheter ablation of the left atrium for the treatment of atrial fibrillation. No atrioesophageal fistula (AEF) has been reported to date with active esophageal cooling, and only one pericardio-esophageal fistula has been reported; however, a formal analysis of the AEF rate with active esophageal cooling has not previously been performed. Methods: Atrial fibrillation abl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…This allowed a significant decrease in the percentage of damaged esophagus, where values of a maximum of 60% were seen in the control case without the use of protection to values of 0% in the protected cases using PEC. This reduction in esophageal injury aligns well with what has been seen with the use of PEC in RF ablation, both in preclinical and mathematical models 6,10,30,31 as well as in published clinical data 32,33 . Although the simplified geometric model has inherent limitations, recent clinical data have been presented with findings suggestive of a beneficial clinical effect from cooling during laser ablation, albeit without having a histopathological correlation on tissue effects.…”
Section: Discussionsupporting
confidence: 80%
“…This allowed a significant decrease in the percentage of damaged esophagus, where values of a maximum of 60% were seen in the control case without the use of protection to values of 0% in the protected cases using PEC. This reduction in esophageal injury aligns well with what has been seen with the use of PEC in RF ablation, both in preclinical and mathematical models 6,10,30,31 as well as in published clinical data 32,33 . Although the simplified geometric model has inherent limitations, recent clinical data have been presented with findings suggestive of a beneficial clinical effect from cooling during laser ablation, albeit without having a histopathological correlation on tissue effects.…”
Section: Discussionsupporting
confidence: 80%
“…Although not yet appearing in the database search, there is one confirmed case of oesophago-pericardial fistula from 25 216 uses. 13 …”
mentioning
confidence: 99%
“…Additionally, our analysis showed that oesophageal cooling was not associated with differences in procedural time, radiofrequency time, acute reconnection index or ablation index. Although retrospective studies of multicentre analysis and device registries have demonstrated a marked reduction of atrioesophageal fistula after the adoption of active oesophageal cooling using the EnsoETM device, 7 , 8 still there is no large randomized controlled study to demonstrate that benefit. Future directions should be guided towards a large randomized trial with long-term follow-up to better evaluate the role of oesophageal cooling in oesophageal injury prevention in patients undergoing AF catheter ablation.…”
mentioning
confidence: 99%